PENCEGAHAN INFEKSI Aeromonas hydrophyla PADA IKAN LELE SANGKURIANG MENGGUNAKAN TEPUNG BUAH MAHKOTA DEWA DALAM PAKAN - Herna Nur Octaviana; ade dwi sasanti; mirna fitrani (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT The pupose of this research was to determine the utilization of phaleria flour as antibacterial to prevent A. hydrophila infection on sangkuriang catfish (Clarias sp.). This research was conducted since September 2014 until Januari 2015 at Laboratorium Budidaya Perairan, Aquaculture study program, Faculty of Agriculture, University of Sriwijaya and Laboratorium UPT Klinik Kesehatan. The research methode used completely randomized design with five treatments and three replications. Catfish fed for 14 days before infection with each treatments, havely 0.6% Â phaleria flour in comersial feed, 0.8% phaleria flour in comersial feed, 1,0 % Â phaleria flour in comersial feed and 1.2 % phaleria flour in comersial feed. Results showed that the treatment of flour Phaleria 1,0% could prevent bacterial infection of A. hydrophila in sangkuriang catfish and produced a prevalence rate 16.37% with the highest survival rate reached 91.67%, the growth weight 3.95 g and length 2.27 cm. Keywords : P.macrocarpa , A. hydrophila, Sangkuriang Catfish